Michel Foucault's Power Relations Theory on al-Maududi's Thought - Maryam, Zuhrotul (Nursyam Center, 2024)
Al Maududi stated that the responsibility for istikhlaf fi al-ardi in the sense of niyabah for God's formal function on earth, must be delegated to a devout believer, it is inappropriate for the responsibility of the caliphate to be given to a munafiq, fasiq and dhalim Muslim. Thus, this research has two objectives, namely first; analyzing al Maududi's thoughts which are reflected specifically in his work Tafhim Al-Qur‘an in Surah an-Nur verses 48-56, which describes the identification of hypocritical people and the criteria for mukhlisin Muslims. Second, to analyze Michel Foucault's social theory of power relations towards the analysis of the genealogical context between al- Maududi and the social context in which the interpretation was produced, so that the idea of al-Maududi's interpretation forms a discourse of knowledge and becomes the truth ideology of the fundamentalist group. This research is classified as qualitative research using the library research approach method. The methodology used is a study of tafsir tahlily based on analysis of primary data sources, namely the interpretation of Tafhim Al-Qur‘an in Surah an Nur verses 48-56. The results of this research conclude that the interpretive analysis used by al Maududi in the letter is classified as sharp and broad argumentative analysis. Tafsir Tafhim Al-Qur‘an has genealogical roots from the Turjuman Al-Qur‘an magazine and the Jamaat-i Islami party. This interpretation is written in two phases; namely the phases before and after the formation of Pakistan. From these two phases, no strikingly different interpretation patterns were found, because in these two phases, al-Maududi remained in a defeated position. Al Maududi's inner conflict struggles can be seen from how he interprets the term munafiq, which in fact Pakistan is a Muslim- majority country but uses a secular government system.